Athletic event-specific characteristics in floating toes during the static standing posture - Yanagiya, T.; Hata, K.; Takeshita, T.; Noro, H.; Yoshida, T.; Koayama, M.; Miyamoto, A. (Journal of Physical Therapy Science, 2020)
[Purpose] We aimed to determine the cause of floating toe syndrome, along with methods for correction and prevention. [Participants and Methods] We recruited 93 Japanese male students. Participants were grouped, according to primary sport, as Sprinters (SPR), Swimmers (SWM), Gymnasts (GYM), Kendoists (KND) and Controls (CON). Degree of floating toe syndrome was measured according to whether any toe was not in full contact with the ground in a static standing posture-the Floating Toe Point (FTP). Two points were given for each toe that was not at the FTP. The sum of the FTP was defined as the Floating Toes Score (FTS), and was classified as follows: Normalcy (over 18 points), Incomplete Contact (between 10 and 17 points), and Floating Toes (Under 9 points). [Results] The mean FTS for all participants (10.40 ± 5.803) met the criteria for Floating Toes. Scores were highest for SWMs (13.46 ± 5.710), followed by GYMs (13.26 ± 4.505), and SPRs (12.00 ± 4.870), who all met the criteria for Incomplete Contact. Both KNDs (6.55 ± 5.409) and CONs (9.45 ± 4.824) met the criteria for Floating Toes. [Conclusion] SWMs had the highest FTSs, followed by GYMs, and SPRs. KNDs had the lowest FTS. However, no group was classified as Normal. We suggest that athletes who practice or train with bare feet do not necessarily have higher FTSs, if evaluated in the standing posture.